Study guides

☆☆

Q: If x equals 2 and y equals 8 then 4x plus 8y equals?

Write your answer...

Submit

Still have questions?

Related questions

(2, 1)

Solve for Y algebraically. 4X + 8Y = 16 8Y = - 4X + 16 Y = - 1/2X + 2 graph and see that the Y intercept = 2

(2xy-4x)+ (8y-16)=2xy-4x+8y-16, which factors as 2(x+4)(y-2)

( 2xy - 4x ) + ( 8y - 16)2 ( xy - 2x ) + 2 ( 4y - 8 ) Answer

4x + y = 9 so that y = 9 - 4x 7x - 8y = 6 7x - 8*(9-4x) = 6 7x - 72 + 32x = 6 39x = 78 x = 2 Then y = 9 - 4x = 9-4*2 = 9-8 = 1

4x + 8y = 20-4x + 2y = -30First add equations 1. & 2. to get:(4x + -4x) + (8y + 2y) = 20 + -30⇒ 10y = -10⇒ y = -1Multiply equation 2. by 4 and subtract it from equation 1:4x + 8y = 20-16x + 8y = -120⇒ (4x - -16x) + (8y - 8y) = 20 - -120⇒ 20x = 140⇒ x = 7Solution x = 7, y = -1Alternatively, to find x, now that y is known to be -1:Substitute y = -1 into equation 1. to give:4x + 8(-1) = 20⇒ 4x -8 = 20⇒ 4x = 28⇒ x = 7The solution can be checked y substituting the values found for x and y in to equation 2. and checking it is the correct value:-4x + 2y = -4(7) + 2(-1)= -28 + -2= -30as required, so the solution is correct.

2

It looks like you have 2 simultaneous equations with 2 variables:4x + 8y = 20 and -4x + 2y = -30. Solution is {x=7, y = -1}.One way to solve:Add the two equations together, combining like terms: (4x - 4x) + (8y + 2y) = 20-30 --> 0 + 10y = -10 --> y = -1. Substitute this into either of the original equations and solve for x=7, then check in the other equation to make sure you calculated correctly.

2xy - 4x + 8y - 16 can be factored.(2xy - 4x) + (8y - 16)2x(y - 2) + 8(y - 2)Since y-2 is the same as the other, it would turn out like this:(2x + 8)(y - 2):]

y = -1

2xy + 4x + 8y + 16 = 2[xy + 2x + 4y + 8] = 2[x(y + 2) + 4(y + 2)] = 2(y + 2)(x + 4)

12y + 2 or 2*(6y+ 1)

16 - 8y = 4xIt is a straight line equation. Graphically, the line two intercept points are:(0, 2) and (4,0)

(2, 3)

Rewrite the equation in the slope intercept form: y = mx + c Thus: 4x - 8y = 12 8y = 4x - 12 y = 4/8x - 12/8 = 1/2x - 3/2 and then, the gradient is the coefficient of x viz 1/2 or 0.5

4x plus 7 plus 3x equals 19 plus xx = 2

4x + 2 + 6 = 2 4x + 8 = 2 4x = -6 x = -6/4 = -3/2

(2, 1)

Need to put in function form. Y =mX + c 6X + 8Y = 12 8Y = - 6X + 12 Y = - 3/4X + 3/2 ----------------------- read off function m = - 3/4 ---------------------slope

8x+5=4x+13 4x=8 x=2 Therefore, your answer is 2.

Do a bit of rearrangement: 1: 10x + 2 = 8y; 2: 8y = 59 - 9x so 10x + 2 = 59 - 9x so 19x - 57 making x = 3 and y is therefore 4.

4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3

X equals 2 :)

(2, 2)

13y+3z+8

People also asked